(untitled) (Clinics, 2014)
OBJECTIVES: Proper assessment of dyspnea is important in patients with heart failure. Our aim was to evaluate the use of the 5-point Likert scale for dyspnea to assess the degree of pulmonary congestion and to determine the prognostic value of this scale for predicting adverse events in heart failure outpatients. METHODS: We undertook a prospective study of outpatients with moderate to severe heart failure. The 5-point Likert scale was applied during regular outpatient visits, along with clinical assessments. Lung ultrasound with ≥15 B-lines and an amino-terminal portion of pro-B-type natriuretic peptide (NT-proBNP) level >;1000 pg/mL were used as a reference for pulmonary congestion. The patients were then assessed every 30 days during follow-up to identify adverse clinical outcomes. RESULTS: We included 58 patients (65.5% male, age 43.5±11 years) with a mean left ventricular ejection fraction of 27±6%. In total, 29.3% of these patients had heart failure with ischemic etiology. Additionally, pulmonary congestion, as diagnosed by lung ultrasound, was present in 58% of patients. A higher degree of dyspnea (3 or 4 points on the 5-point Likert scale) was significantly correlated with a higher number of B-lines (p = 0.016). Patients stratified into Likert = 3-4 were at increased risk of admission compared with those in class 1-2 after adjusting for age, left ventricular ejection fraction, New York Heart Association functional class and levels of NT-proBNP >;1000 pg/mL (HR = 4.9, 95% CI 1.33-18.64, p = 0.017). CONCLUSION: In our series, higher baseline scores on the 5-point Likert scale were related to pulmonary congestion and were independently associated with adverse events during follow-up. This simple clinical tool can help to identify patients who are more likely to decompensate and whose treatment should be intensified.